2021
DOI: 10.3390/su13052667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Melting Performance in a Conical Latent Heat Thermal Unit Having Variable Length Fins

Abstract: A conical shell-tube design with non-uniform fins was addressed for phase change latent heat thermal energy storage (LHTES). The shell was filled with nano-enhanced phase change material (NePCM). The cone aspect ratio of the shell and the fins aspect ratio were adopted as the geometrical design parameters. The type and volume fraction of the nanoparticles were other design parameters. The investigated nanoparticles were alumina, graphite oxide, silver, and copper. The finite element method was employed to solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Here, f -liquid fraction; ε-a small computational constant used to avoid division by zero (normally it is taken a number less 0.001); ρ 0 -density at T 0 , kg/m 3 ; A mush -constant of mushy zone, generally it is (10 4 ~10 7 ) kg/(m 3 •s) [44]. However, Shmueli et al [45] concluded by comparing with the experiment that when A mush takes 10 8 kg/(m 3 •s), it is more accurate for the simulation of the paraffin melting process.…”
Section: Momentum Conservation Equationmentioning
confidence: 99%
“…Here, f -liquid fraction; ε-a small computational constant used to avoid division by zero (normally it is taken a number less 0.001); ρ 0 -density at T 0 , kg/m 3 ; A mush -constant of mushy zone, generally it is (10 4 ~10 7 ) kg/(m 3 •s) [44]. However, Shmueli et al [45] concluded by comparing with the experiment that when A mush takes 10 8 kg/(m 3 •s), it is more accurate for the simulation of the paraffin melting process.…”
Section: Momentum Conservation Equationmentioning
confidence: 99%